COMBINATION EFFECTS OF -GLUCAN ORIGINATED FROM AUREOBASIDIUM AND PLATYCODIN ON THE OBESE DB/DB MOUSE - # # Jae-Suk Choi; Joo Wan Kim; Go-Woon Jung; Dong-Chan Park; Hyung-Rae Cho; Sae Kwang Ku; Jae-Hak Sohn (Journal of Animal and Plant Sciences, 2018)
To find out the fittest composition, the anti-obesity effects of 11 types of the 2-glucan compositions and platycodin (PLAT) (MPP) were observed in the obese db/db mouse at 200mg/kg-dosing levels with 2-glucan or PLAT single formula, respectively. Test materials were administered orally once a day for 28 days. Each of seven mice per group was selected using blood glucose levels and body weight, and the changes in the body weight, epididymal fat weights, serum adiponectin and leptin levels, adipose adiponectin contents and liver triglyceride contents were monitored. The weights of epididymal fats, serum leptin levels and liver triglyceride contents in db/db control were significantly (p<0.01) increased compared to that of db/m with significant (p<0.01) decrease in serum adiponectin levels and adipose adiponectin contents. However, these obese changes were dramatically decreased after 2-glucan single, PLAT single and some MPP-dosing and the changes related to the obese showed decreased trends along increasing the 2-glucan composition. Synergic anti-obesity effects were restricted to the MPP 1:1 formulation compared to those of single formulas, respectively. The synergic anti-obesity effects detected in MPP 1:1 formulation were considered as results of the similar anti-obesity mechanisms of 2-glucan and PLAT that inhibit the intestinal absorption of fats. As a consequence, there is an expected increase in
Keywords: 2-Glucan; Platycodin; db/db mouse; obesity; adipokine; composition.